The Effect of Giving Rewards and Punishment on Employee Performance at the Bandar Lampung State Administrative Court - Restalina, Sherli; Candra, Ade (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research aims to test and explain the influence of rewards on employee performance, the influence of punishment on employee performance, and the influence of rewards on punishment at the Bandar Lampung State Administrative Court. The population in this study were all employees of the Bandar Lampung State Administrative Court, totaling 42 people. This research uses a quantitative approach, and the sample selection technique is carried out using a saturated sampling method because the samples used are all members of the population. The data collection technique uses a questionnaire, and measurement uses a Likert scale. The data processing and analysis technique used in this research is multiple linear regression analysis using IBM SPSS Statistics 17 software. The results of the research analysis show that there is a simultaneous correlation between reward and punishment on employee performance. Segmentally, rewards have a significant positive influence on employee performance, while punishment does not have a significant influence on employee performance.